Voluntary Financial Disclosure to Downward Stakeholders: An Empirical Examination of Chinese Nonprofits. Issue 1 (2nd January 2020) - Hu, Ming; Zhu, Jiangang; Kong, Dejie
Abstract: Downward financial disclosure in the nonprofit sector is little scrutinized in the extant literature where most studies focus on financial disclosure "upward" to regulators, governing bodies, and donors. Analyzing a sample of 311 nonprofits collected in China, this article examines the determinants of nonprofits' financial disclosure downward to their staff, beneficiaries, and the general public. The authors claim that in addition to the four sets of factors—organizational strategy, capacity, governance, and environment—organizational culture also affects nonprofits' voluntary financial disclosure. In addition, there are different decision-making patterns of financial disclosure to the three downward stakeholders. While disclosure to staff is associated with strategy and internal governance, disclosure to beneficiaries is associated with internal governance, and disclosure to the general public is associated with strategy, capacity, and organizational culture.